The Reality of Smart Leadership in the Iraqi Basketball Federation in Organizing Tournaments and Matches from Workers’ Perspectives - Sehen , Khairiyah; Alia , Wasan; Aziz , Tamader (Journal of Physical Education, 2025)
This study aimed to identify the level of smart leadership in organizing basketball tournaments and matches from the point of view of those working on its management. A descriptive correlational design was used to guide his study. The limits of the research community are represented by those working on the management of the Iraqi Basketball Federation championships including (head and members of sub-federations, committees, local referees, coaches, and administrators of clubs) for the sports season (2023-2024) in 14 Iraqi governorates, except Kurdistan Region (N = 557). The main research sample is 267 individuals who were selected for application who account for (47.935%) of this community. After determining the measurement tool, the researchers conducted the survey by applying the smart leadership scale in organizing basketball tournaments and matches on the members of the application sample by conducting the main survey on them and directly measuring them in a collective and individual manner for the period from December 3rd, 2023 to January 4th, 2024. After collecting the data and statistically processing it with the SPSS, the conclusions and recommendations were that the tournaments and matches organizers of the Iraqi Basketball Federation have a positively acceptable level of smart leadership from the point of view of those working on managing the Iraqi Basketball Federation championships. The point of view of those working on managing the Iraqi Basketball Federation championships has achieved an advanced level of organizational intelligence among those in charge of organizing the Iraqi Basketball Federation tournaments that raise the level of smart leadership they have. The point of view of those working on managing the Iraqi Basketball Federation championships has achieved an advanced level of organizational intelligence among those responsible for organizing the Iraqi Basketball Federation tournaments that raise the level of smart leadership they have. Raising the level of smart leadership in organizing basketball tournaments and matches requires increased attention to supporting emotional intelligence, according to the point of view of those working on managing the Iraqi Basketball Federation’s championships. It is necessary to work to empower those responsible for organizing the Iraqi Basketball Federation championships to raise the level of emotional intelligence because of its importance in raising the level of smart leadership for them. The Iraqi Basketball Association needs to take care in accrediting qualified academics specialized in sports management, adopting opportunities to develop the capabilities of those responsible for organizing the Iraqi Basketball Federation championships.